Local Wisdom of Bulalo Mangrove Forest Management, Kwandang District, North Gorontalo Regency. - Ruruh, Alexander; Suma, Zeinab Nurlena Y. (Journal of Selvicoltura Asean, 2024)
Local Wisdom is a form of environmental wisdom in social life in a place or region. So, it refers to a particular locality and community. This research aims to determine local wisdom and community dependence on forest management in Bulalo Village, Kwandang District, North Gorontalo Regency. The research method used was Snowball sampling with 15 respondents, consisting of 1 Pante Hamlet Head, 1 traditional leader, 7 Fishermen/Farmers, and 6 Farmers. Types of Mangroves in Bulalo Village, there are 5 types of mangrove vegetation, namely Wu’ata (Rhizophora sp.), Tangalo (Ceriops sp.), Tamenda’o (Sonneratia sp.), Songge (Bruguierra sp.) and Yapi-yapi (Avicennia sp.). Mangrove farming groups and local communities have long implemented this belief or taboo. They think that these methods must be implemented to maintain and avoid damage to the mangrove forests in Tuwoto Village, Kwandang District, North Gorontalo Regency. Plant parts that are often used are roots, fruit, sap, and leaves.